ChemInform Abstract: A General and Efficient Method to Convert Selenides into Selenones by Using HOF·CH3CN. Issue 5 (4th February 2014) - Potash, Shay; Rozen, Shlomo
Abstract The first general method for mild and efficient synthesis of selenones including sterically hindered and electron‐deficient ones is reported.